Short Communication: Mollusks biodiversity of Lake Sevan, Armenia - IRINA V. MASHKOVA; TATYANA G. KRUPNOVA; ANASTASIYA M. KOSTRYUKOVA; LAURA J. HARUTYUNOVA; HOVHANNISYAN S. VARUZHAN; NIKITA E. VLASOV (Society for Indonesian Biodiversity, 2018)
Mashkova IV, Krupnova TG, Kostryukova AM, Harutyunova LJ, Varuzhan HS, Egorov NO. 2018. Short Communication: Mollusks biodiversity of Lake Sevan, Armenia. Biodiversitas 19: 1509-1513. The paper considers mollusks biodiversity in the freshwater lakes of Lake Sevan, Armenia. Lake Sevan is the largest water body in Armenia and one of the largest freshwater lakes in Eurasia. Since 1930 it has been actively used for irrigating Ararat plain and in hydropower. So, its water level fell by 20 m, and its volume became 40% less. Since mid-2000 when two tunnels had been built water level started to grow. For the last 6 years, water level was reported to grow. As a result of our study, 11 aquatic mollusks species (10 gastropod and 1 bivalve taxa) were currently found living in the Sevan lake. We found Lymnaea stagnalis (Linnaeus, 1758), Radix auricularia (Linnaeus, 1758), R. tumida (Held, 1836), R. balthica (Linnaeus, 1758), R. lagotis (Schrank, 1803), Galba truncatula (O. F. Müller, 1774), Planorbis planorbis (Linnaeus, 1758), Bathyomphalus contortus (Linnaeus,1758), Gyraulus acronicus (Férussac, 1807), Valvata piscinalis (O. F. Müller, 1774), Euglesa casertana (Poli, 1791). Lymnaeidae represented the largest number of species. The most abundant species was Lymnaea stagnalis (Linnaeus, 1758).